Sarpogrelate hydrochloride ameliorates diabetic nephropathy associated with inhibition of macrophage activity and inflammatory reaction in db/db mice. - Eun Soo Lee; Mi Young Lee; Mi-Hye Kwon; Hong Min Kim; Jeong Suk Kang; You Mi Kim; Eun Young Lee; Choon Hee Chung (PLoS ONE)
The aim of this study was to evaluate the effects of sarpogrelate hydrochloride (SH), a selective serotonin 2A receptor antagonist, on diabetic nephropathy in a type 2 diabetes mouse model. We treated db/m and db/db mice with SH (30 mg/kg/day) for 12 weeks. Rat renal proximal tubule cells (NRK-52E) and mouse macrophages (Raw 264.7) were stimulated by high glucose (30 mM glucose) or LPS (100 ng/ml) with or without SH (20 μM). We found that SH treatment increased serum adiponectin level and decreased urinary albumin, macrophage infiltration to glomeruli, and renal inflammatory and fibrosis signals, which were highly expressed in diabetic mice. Proximal tubule cells treated with high glucose (30 mM) also showed increased inflammatory and fibrosis signals. However, SH (20 μM) treatment reduced these changes. Moreover, SH treatment inhibited LPS-stimulated macrophage migration and activation. These findings suggest that SH ameliorates diabetic nephropathy not only by suppressing macrophage infiltration, but also by anti-inflammatory and anti-fibrotic effects.